MARKETING DIGITALIZATION AND RELIGIUSITY AND ITS INFLUENCE ON INTEREST IN MUZAKKI FUNDRAISING SMILE MANDIRI PURWAKARTA - Ade Nurhayati Kusumadewi; Ropi Marlina; Rika Amalia (STIESA Press, 2023)
The purpose of this study is to find out whether digital marketing affects the interest of muzaki ziswaf in fundraising independent smile Purwakarta, whether religiosity affects the interest of muzaki ziswaf in fundraising independent smile Purwakarta. The method used in this study is a quantitative with descriptive verification method. The data analysis technique used is multiple linear regression with SPSS software version 25. The sampling method used is purposive sampling, which uses several criteria so that there are muzakki fundraising senyum mandiri Purwakarta, aged 19-50 years, domiciled in Purwakarta, one respondent can only fill out one questionnaire. The results showed that both free variables simultaneously have a significant effect on bound variables. Of the total dependent variables, 60.3% simultaneously affected the interest of muzaki ziswaf Senyum Mandiri Purwakarta.